A Critique on “Economic Threats and Resistance Economy” - Seyyed Shamseddin Hosseini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper aims to review the “Economic Threats and Resistance Economy”. The authors believe that economic war (sanctions) is the main threat to Iran’s economy that is an instrument of exercising power. It is also noted that the economy is more vulnerable to sanctions in cyber areas, science, and technological dependency in industrial areas and economic dependency on oil sector. Among offered proposals, establishing an economic defense system and base is more applicable.The authors’ effort on finding the links among economy, defense, and security is the most important advantage of the book. However, the book could be enhanced in terms of its statistical analysis, credibility of some references, and old statistics usage.Although the title mentions resistance economy, the text does not perpend on general policies of resistance economy. It is necessary to pay more attention to requirements and consistency of resistance economy patterns, comprehensive defense, and security pattern and its role in resistance economy. The book could be used as a secondary reference for courses like Iran’s economy and development economics. Nevertheless, a basic move is to establish academic fields like defensive economics in graduate level.